Performance evaluation of cocoa marketing in Osun State, Nigeria - Joseph Olumide Oseni; Adewale Isaac Olutumise; Boluwaji Olusola Olutumise (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
This paper appraised cocoa marketing performance in Osun State, Nigeria. The study specifically examined the costs and returns associated with cocoa marketing, and determined factors affecting cocoa marketing performance in the area. Primary data were used and collected through a well structured questionnaire and focus group discussion session. A multistage sampling procedure was employed to randomly select 120 respondents for the study. The analytical tools used were: descriptive statistics, budgetary analysis and Seeming Unrelated Regression Equation (SURE).The results of costs and returns using budgetary analysis showed that cocoa marketing is a profitable enterprise with a Return on Investment (ROI) of 1.36 which implies that cocoa marketer will realize 36Kobo on each naira expended. Again, percentage profit of over 35% further confirmed that cocoa marketing is a highly profitable venture in the study area. The SURE results showed that age of the cocoa marketers, marital status, household size, years of education, years of marketing experience, marketer institution group, depreciation cost on fixed inputs, number of stores, cost of labour, cost of transportation, season of sales, cocoa bean quality and incidence of theft were statistically significant factors affecting performance of cocoa marketing in the study area.